Detection Of Antibiotic Residues In Quail Eggs At The Traditional Market Of Mataram City - Nurul Khairah; Kholik Kholik (Universitas Pendidikan Mandalika, 2022)
Quail farms (Coturnix sp.) are inseparable from the antibiotic uses, breeders who use antibiotics without observing the appropriate rules could cause residues in the tissues and organs of animals, including in eggs. Consumption of quail eggs containing by antibiotic residues could have a negative impact on health. Quail eggs consumed by the public generally come from traditional markets. The survey results show that the Karang jasi market is a traditional market in Mataram city that sells the most quail eggs. This study aimed to detect antibiotic residues in quail eggs in the traditional market of Mataram city. This research was a descriptive study, used the survey method with a cross-sectional approach. 18 Samples were taken from the traditional market of Mataram city which is sells the most quail eggs. The examination of samples was done qualitatively using a screening test by bioassay. The test results showed that all samples tested were negative from antibiotic residue. Based on the result, could be councluded that the quail eggs in the karang jasi traditional market are safe for consumption.